Analysis of the Community’s Willingness to Pay (WTP) for the Protection of Mangroves in Kuala Langsa, Aceh - Zuriana Siregar; Syamsuardi Syamsuardi; Azwar Rasyidin; Eni Kamal (Universitas Andalas, 2019)
Mangrove, as one of the most unique ecosystems, is a great natural resource potential with high productivity and biodiversity able to adapt to harsh areas between the sea and coast. Its destruction rate is very mild as it is estimated to 1% each year (Ong et al., 1991) and 0.7-3% per year (Pedleton et al., 2012). The destruction of mangrove is usually related with human population density (Alongi, 2002). Widespread mangrove destruction affects the loss of biodiversity and other resources and the functioning of the ecosystem. The huge potential of mangrove must be preserved by managing, maintaining and providing costs to protect and improve ecosystems. This study aims to measure Kuala Langsa community members’ willingness to pay for the preservation and repairationof degrading mangrove. To achieve this goal, Contingent valuation methods was used in this study. Of the 131 respondents involved in this study, 112 or 85.496% are willing to pay for the preservation of mangrove. While those unwilling to pay account for 19 or 4.504% . WTP with the households 669 earned by is Rp 18,821,512,200/month or Rp 225,858,146,400/year.